2019
DOI: 10.1080/21691401.2019.1593853
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 regulates osteoarthritis chondrocyte apoptosis via WNT3/β-catenin signalling

Abstract: Objective: Cyclin D1 was an important molecular involved in the pathological process of osteoarthritis (OA). The purpose of this study was to identify the effect and potential mechanism of Cyclin D1 for the proliferation and apoptosis of OA chondrocytes. Methods: We used polymerase chain reaction (PCR) method to identify the expression levels of Cyclin D1 and downstream Wnt/b-catenin pathway-related genes in OA chondrocytes according to the grade of OA. Small interfering RNA (siRNA) or overexpression of Cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…All of them are highly expressed in TCam-2 in our previous RNA-Seq screens (Smialek et al, 2019 preprint). Our analysis showed that KIF18A knockdown caused a significant downregulation of the mRNA level of BCL2, an antiapoptotic gene (Petros et al, 2001), and upregulation of antiapoptotic (Chen et al, 2019;Singh et al, 2019) CCND1 and PIK3CA. Upregulation of the pro-apoptotic shorter isoforms of BCL2L1 mRNA occurring upon KIF18A knockdown was in line with the pro-apoptotic effect of KIF18A knockdown, as with downregulation of anti-apoptotic BCL2 (Fig.…”
Section: Knockdown Of Kif18a Causes a Decrease In Proliferation Of Tcmentioning
confidence: 70%
“…All of them are highly expressed in TCam-2 in our previous RNA-Seq screens (Smialek et al, 2019 preprint). Our analysis showed that KIF18A knockdown caused a significant downregulation of the mRNA level of BCL2, an antiapoptotic gene (Petros et al, 2001), and upregulation of antiapoptotic (Chen et al, 2019;Singh et al, 2019) CCND1 and PIK3CA. Upregulation of the pro-apoptotic shorter isoforms of BCL2L1 mRNA occurring upon KIF18A knockdown was in line with the pro-apoptotic effect of KIF18A knockdown, as with downregulation of anti-apoptotic BCL2 (Fig.…”
Section: Knockdown Of Kif18a Causes a Decrease In Proliferation Of Tcmentioning
confidence: 70%
“…Thus, more experiments are needed to explore the effect of WNT3 overexpression on trophoblast proliferation. Some researchers have found similar phenomena in breast cancer cell lines, esophageal squamous cell carcinoma cell lines, and osteoarthritic chondrocyte cell lines, in which expression of nuclear β-catenin was decreased and the Wnt/β-catenin signaling pathway was suppressed after knockdown of WNT3 [ 37 39 ]. Thus, WNT3 may be an activator of the Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 83%
“…10b). Some researchers have found similar phenomena in breast cancer cell lines, esophageal squamous cell carcinoma cell lines and osteoarthritic chondrocyte cell lines, in which expression of nuclear β-catenin was decreased and the Wnt/β-catenin signaling pathway was suppressed after knockdown of WNT3 [37][38][39]. Thus, WNT3 may be an activator of the Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 79%